Kemuliaan Sunan Ambu Refleksi Masa Kini Sebagai Ide Penciptaan Karya Lukis - Maheswari, Searsa Nur Aulia; Supriatna, Supriatna; Kusdiana, Hilman Cahya (Jurusan Seni Rupa ISBI Bandung, 2025)
This creation recontextualizes the noble values of women in Sundanese culture through the medium of painting, by combining the visual strength of traditional culture through a modern aesthetic approach, in this case the mythological figure of Sunan Ambu as the main source of ideas, which is seen as having values of nobility, compassion, wisdom, justice, blessing and help. The figure of Sunan Ambu is metaphorized into a female figure in expressionism style. The process of this work uses the practice led research method, which is the process of creating works through observation, exploration of forms and techniques, strengthening the main idea and implementing the concept so as to produce works as artistic expressions related to the issue of shifting values of women today.